2017
DOI: 10.1177/1535370217724790
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of parasympathetic or sympathetic denervation on intestinal epithelial cell proliferation and apoptosis

Abstract: This study investigates the long-term effect of autonomic denervation on intestinal epithelial cell turnover, as measured by proliferation, apoptosis, and total cell number. Although previous research has established that autonomic denervation can alter intestinal epithelial turnover under short-term conditions, here we establish for the first time that these changes do not persist long-term when you control for surgical-induced changes in food intake and use targeted denervation procedures. These findings add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…These results indicate that the vagus nerve is required for the orexigenic effects of ghrelin when tested during the natural rodent feeding cycle (onset of dark cycle). SDV animals weighed significantly less than sham animals at the start of the IP ghrelin experiment (Sham: 409.8g +/-8.5; SDV: 362.6g +/-9.5; p<0.05) even after an extended post-surgical recovery period, as we have previously shown [25]. However, while SDV animals ate significantly less overall compared with the sham animals ( Fig.…”
Section: Vagus Nerve Signaling Is Required For the Hyperphagic Effectsupporting
confidence: 67%
See 1 more Smart Citation
“…These results indicate that the vagus nerve is required for the orexigenic effects of ghrelin when tested during the natural rodent feeding cycle (onset of dark cycle). SDV animals weighed significantly less than sham animals at the start of the IP ghrelin experiment (Sham: 409.8g +/-8.5; SDV: 362.6g +/-9.5; p<0.05) even after an extended post-surgical recovery period, as we have previously shown [25]. However, while SDV animals ate significantly less overall compared with the sham animals ( Fig.…”
Section: Vagus Nerve Signaling Is Required For the Hyperphagic Effectsupporting
confidence: 67%
“…These findings are consistent with a previous report by Date et al [7], which found that both SDV and chemical vagal deafferentation attenuate the hyperphagic effect of ghrelin. However, in the study by Date and colleagues the evaluation of ghrelin-stimulated hyperphagia occurred before the complete recovery from SDV surgery, which is critical for the return to feeding behavior and other physiological functions after vagotomy [25,[49][50][51]. In contrast, Arnold et al, reported that SDV has no effect on ghrelin-mediated hyperphagia in rats [52].…”
Section: Previous Work Shows That Ghrelin Blocks the Downregulation Omentioning
confidence: 98%
“…After SNS or PNS denervation, epithelial cell proliferation has either decreased [130,133,134,135] or increased [136]. Results are time dependent and effects seem to recover due to compensatory mechanisms, such as upregulation of adrenergic or cholinergic receptor expression, compensation by non-denervated branch, and modulation of the ENS [137]. No data exist on a change in epithelial cell proliferation after sympathetic or parasympathetic stimulation, rather than denervation.…”
Section: The Impact Of the Autonomic Nervous System On Intestinal mentioning
confidence: 99%
“…These data indicated that blocking the SNS decreased proliferation and differentiation of intestinal stem cells. Experiments using pharmacological and surgical approaches to disrupting the SNS, showed that disruption of the SNS or the PNS, either decreased or increased mitotic rates, depending on the time frame of drug action (Davis et al, 2017). These results indicate that the autonomic nervous system can affect the mitotic kinetics of intestinal epithelial cells under physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%